2014
DOI: 10.3350/cmh.2014.20.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy induced liver abnormalities: an imaging perspective

Abstract: Treating patients undergoing chemotherapy who display findings of liver toxicity, requires a solid understanding of these medications. It is important for any clinician to have an index of suspicion for liver toxicity and be able to recognize it, even on imaging. Cancer chemotherapy has evolved, and newer medications that target cell biology have a different pattern of liver toxicity and may differ from the more traditional cytotoxic agents. There are several hepatic conditions that can result and keen clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 31 publications
2
53
0
Order By: Relevance
“…Regarding CBC, the difference between mean 1 and 2 of total WBC and ANC in group 1 was statistically significant (3016±807/mm 3 vs. 3478±891/mm 3 and 1562±650/mm 3 vs. 2067±977/mm 3 , respectively) (p=0.015 and 0.034, respectively). In other words, the mean WBC count and ANC during the 6-month period after vitamin E withdrawal were significantly higher than those during the period when vitamin E was being used.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Regarding CBC, the difference between mean 1 and 2 of total WBC and ANC in group 1 was statistically significant (3016±807/mm 3 vs. 3478±891/mm 3 and 1562±650/mm 3 vs. 2067±977/mm 3 , respectively) (p=0.015 and 0.034, respectively). In other words, the mean WBC count and ANC during the 6-month period after vitamin E withdrawal were significantly higher than those during the period when vitamin E was being used.…”
Section: Resultsmentioning
confidence: 87%
“…While this function predisposes liver to damage, some medications are identified that induce liver damage more commonly than others (1,2). The liver damage induced by chemotherapy agents can manifest in a number of forms varying from an asymptomatic patient with mild elevation in transaminases on laboratory study to a severely ill patient presenting with a condition such as acute viral hepatitis (3). Methotrexate (MTX) is an anti-metabolite agent that inhibits folate metabolism and can be used for different indications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various classes of chemotherapeutic agents have been associated with hepatic lesions such as steatosis, steatohepatitis, sinusoidal obstruction syndrome, acute hepatitis, and liver necrosis ( 2 ) . Oxaliplatin-based treatments are most often associated with sinusoidal obstruction syndrome and regenerative nodular hyperplasia ( 2 , 3 ) .…”
mentioning
confidence: 99%
“…Oxaliplatin-based treatments are most often associated with sinusoidal obstruction syndrome and regenerative nodular hyperplasia ( 2 , 3 ) .…”
mentioning
confidence: 99%